PKM massage sport pada pengurus Masjid SC Ar-Riyadhoh Makassar - Ricardo Valentino Latuheru; Muh.Syahrul Saleh; Andi Rizal; Benny B (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The issue of community service is as follows: Knowledge and understanding of the Massage sport movement technique is not yet known by the administrators of the SC Ar-Riyadhoh Makassar Mosque. Most only know massage in general. Therefore, through this training and counseling can provide an overview and knowledge of the techniques of sports massage movements. The community partnership program activities are divided into two activities, namely: First, providing an understanding of the definition, purpose and benefits of providing sports massage to the Managers of the SC Ar-Riyadhoh Makassar Mosque through lectures. Second, giving material about the basic techniques of sports massage.Third, direct practical activities of the basic techniques of Massage Sport with some examples of activities. Fourth, giving individual tasks that must be done by each participant for the development and mastery of the sports massage movement for personal performance. The results of the development of this sports massage must be reported to be evaluated so that it can really be used as a guide to doing a true and ideal sports massage. From the results of the implementation of this activity found the answer that the interest of SC AR-Riyadhoh Makassar Makassar Mosque officials to find additional training knowledge about the basic techniques of Massage Sport with many variations of movement is very high. So that their enthusiasm in following the material, both when the theory and practice of the sports massage movement is maintained and never reduce their motivation in participating in the training activities because the training is considered very useful for themselves and others.